COL1A2 Polymorphism contributes to Oral submucous fibrosis: A possible role in inducing alternative splicing in areca chewers. Issue 2 (20th August 2020) - Katarkar, Atul; Roy, Ushapati; Mukherjee, Sanjit; Ray, Jay G.; Chaudhuri, Keya
Abstract: Oral submucous fibrosis (OSMF) is a chronic inflammatory disease of the oral cavity but the pathogenesis of the disease is still uncertain among the areca nut chewers. Every chewer does not show up with fibrotic changes that further extend to genetic basis of OSMF pathogenesis. Genetic predisposition has been now identified as a major risk factor for increasing the susceptibility toward the disease among these chewers. In this study, two single nucleotide polymorphism (SNP) of COL1A2 rs42542 (Exon 28, G1645C) and rs421587 (Intron 28, 665+15A>G) showing mRNA splice variant trait with exon 28 skipping, extended exon 28 and intron 28 retention. The polymorphisms of the COL1A2 gene was identified by polymerase chain reaction‐direct genomic DNA sequencing from 187 patients with OSMF and 188 control participants matched on age, gender, and ethnicity. COL1A2 alternative splice variants from mRNA in human oral biopsy tissues obtained from OSMF patient and controls were confirmed by using reverse transcription PCRs (RT‐PCRs). Significant genotypic associations were observed for an exon 28 SNP (GC; P < [OR‐2.35; CI 1.44‐3.83; P < .001] and CC [OR‐6.99; CI 1.83‐31.24; P = .001) induces Ala to Pro substitution at amino acid 459 of COL1A2 in OSMF patients. Exon skipping is significantly associated with both the SNPs. Our results confirm the role of rs42542 and rs421587 in COL1A2 alternative splicing and support a strong role in susceptibility to OSMF, and could have served as surrogate markers.